A comparison of rolling averages versus discrete time epochs for assessing the worst-case scenario locomotor demands of professional soccer match-play. Issue 8 (August 2020) - Fereday, Kieran; Hills, Samuel P.; Russell, Mark; Smith, Jordan; Cunningham, Dan J.; Shearer, David; McNarry, Melitta; Kilduff, Liam P.
Abstract: Objectives: To compare fixed epochs (FIXED) and rolling averages (ROLL) for quantifying worst-case scenario ('peak') running demands during professional soccer match-play, whilst assessing contextual influences. Design: Descriptive, observational. Methods: Twenty-five outfield players from an English Championship soccer club wore 10-Hz microelectromechanical systems during 28 matches. Relative total and high-speed (>5.5 m s −1 ) distances were averaged over fixed and rolling 60-s to 600-s epochs. Linear mixed models compared FIXED versus ROLL and assessed the influence of epoch length, playing position, starting status, match result, location, formation, and time-of-day. Results: Irrespective of playing position or epoch duration, FIXED underestimated ROLL for total (∼7–10%) and high-speed (∼12–25%) distance. In ROLL, worst-case scenario relative total and high-speed distances reduced from 190.1 ± 20.4 m min −1 and 59.5 ± 23.0 m min −1 in the 60-s epoch, to 120.9 ± 13.1 m min −1 and 14.2 ± 6.5 m min −1 in the 600-s epoch, respectively. Worst-case scenario total distance was higher for midfielders (∼9−16 m min −1 ) and defenders (∼3–10 m min −1 ) compared with attackers. In general, starters experienced higher worst-case scenario total distance than substitutes (∼3.6–8.5 m min −1 ), but lower worst-case scenario high-speed running over 300-s (∼3 m min −1 ). Greater worst-case scenario total and high-speed distances were elicited during wins (∼7.3–11.2 m min −1 and ∼2.7–7.9 m min −1, respectively) and losses (∼2.7–5.7 m min −1 and ∼1.4–2.2 m min −1, respectively) versus draws, whilst time-of-day and playing formation influenced worst-case scenario high-speed distances only. Conclusions: These data indicate an underestimation of worst-case scenario running demands in FIXED versus ROLL over 60-s to 600-s epochs while highlighting situational influences. Such information facilitates training specificity by enabling sessions to be targeted at the most demanding periods of competition.